(untitled) (Multi-disciplinary Journal of Research and Development Perspectives, 2026)
Nigeria is richly endowed country with formidable natural, psychical and human resources. Joining the league of newly minted states in 1960, Nigeria offered the continent and blacks everywhere a future that was promissory, resplendent and anchored on a vision of rapid development. with annual budget of #9.12 trillion in 2018, #8.92 trillion in 2019 and #10.33trillion for the year 2020. The oil price has been oscillating from 61 to 66 in recent times, it is expected that Nigeria should have out grown its present description of a developing economy. Successive administration has come with promises of improving the standard of living of its residents during electioneering campaigns. The military are not left out in the governance of the country, yet lack of adequate electricity supply, poor roads network, lack of infrastructure (Health facilities) and absent of social amenities like affordable water have bedevil the country. The agricultural development plans are only hard on radio, without any practical improvement, this explain the high level of hunger in the land, the same reason for the rising and unending insurgency. The questions is, what is happening to the public revenue, how are the issues of social welfare handled, and what is the space of industrialization in Nigeria, this paper attempt to x-ray this paradigms, with the view of availing more literature on the indices of public finance, social welfare and industrial development in Nigeria